2010
DOI: 10.1093/sleep/33.6.811
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Blood-Flow Responses to Hyperoxia and Hypercapnia in Men with Obstructive Sleep Apnea

Abstract: This study showed unimpaired choroidal vascular reactivity in otherwise healthy men with OSA. This suggests that patients with OSA, without comorbidities, have long-term adaptive mechanisms active in ocular microcirculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 58 publications
(90 reference statements)
1
18
0
1
Order By: Relevance
“…They reported that all of the OSAS patients were newly diagnosed, and that the cause of the lack of deterioration in the choroidal flow may have been still intact autoregulatory mechanisms. Tonini et al 13 found similar choroidal blood flow reactivity to CO 2 and O 2 in the OSAS patients and controls in their prospective study, and concluded that ocular microcirculation, which provides adaptive mechanisms, continues long-term in OSAS patients. Contrarily, Xin et al 12 observed significantly lower measurements in severe OSAS patients with regard to the subfoveal and nasal choroidal thicknesses, when compared with the mild-moderate OSAS patients and control subjects.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…They reported that all of the OSAS patients were newly diagnosed, and that the cause of the lack of deterioration in the choroidal flow may have been still intact autoregulatory mechanisms. Tonini et al 13 found similar choroidal blood flow reactivity to CO 2 and O 2 in the OSAS patients and controls in their prospective study, and concluded that ocular microcirculation, which provides adaptive mechanisms, continues long-term in OSAS patients. Contrarily, Xin et al 12 observed significantly lower measurements in severe OSAS patients with regard to the subfoveal and nasal choroidal thicknesses, when compared with the mild-moderate OSAS patients and control subjects.…”
Section: Discussionmentioning
confidence: 83%
“…Snoring is the most common symptom in 19,20 . Increased sympathetic system, endothelial, and autonomic dysfunctions have been shown in OSAS patients, and choroidal microcirculation, which is maintained by autonomic regulation, may be impaired as a result of one or more of these altered mechanisms 11,13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] Other studies have found unimpaired choroidal vascular reactivity in otherwise healthy men with obstructive sleep apnea. 33,34 Because other systemic comorbidities such as diabetes and hypertension exist in this population, further investigation of sleep apnea in PCV is required. Our data support querying PCV patients regarding a history of sleep-disordered breathing; those with positive symptoms or a history of sleep apnea should be referred for diagnostic sleep testing or sleep apnea management.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of CAVI has demonstrated good reproducibility and was not affected by the blood pressure during measurement 17,18) . To date, the majority of studies linking OSA to arterial stiffness recruited participants from sleep clinic patients [19][20][21] , there have been only two communitybased studies 22,23) , which also recruited patients with sleep disorder breathing and their methodology to measure arterial stiffness was different to CAVI.…”
Section: Assessment Of Nihmentioning
confidence: 99%